If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -17 = 2x + 4 Reorder the terms: -17 + 4x = 2x + 4 Reorder the terms: -17 + 4x = 4 + 2x Solving -17 + 4x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -17 + 4x + -2x = 4 + 2x + -2x Combine like terms: 4x + -2x = 2x -17 + 2x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -17 + 2x = 4 + 0 -17 + 2x = 4 Add '17' to each side of the equation. -17 + 17 + 2x = 4 + 17 Combine like terms: -17 + 17 = 0 0 + 2x = 4 + 17 2x = 4 + 17 Combine like terms: 4 + 17 = 21 2x = 21 Divide each side by '2'. x = 10.5 Simplifying x = 10.5
| f(x)=8cosx | | -4y-9=6y+11 | | -2x^2-x=20 | | 11/2X=10 | | X^2+2x+4=3 | | 3(x+5)+2x=5x-15 | | 6x+7x+8=540 | | x^2-(m+1)*x+m=0 | | x^5-7x^3+9x=-x | | 6x+7x+8=360 | | x/187 | | (8,3)x= | | 3(10+x)=3 | | 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x | | x-[5+3x-[5x-(6+x)]]=-3 | | 2X=4/15 | | 6x+1=3x+4 |